Idiomatic expressions of places in British English and Vietnamese as seen from cultural perspective = Cách diễn đạt thành ngữ về nơi chốn trong tiếng Anh và tiếng Việt nhìn từ góc độ văn hóa. M.A Thesis Linguistics: 60 22 15 - Hà, Thị Thọ Anh (University of Languages and International Studies, 2017)
British English and Vietnamese have their own valuable treasures of idioms as well as their great values of culture and language that are handed down and enriched from generation to generation. Idiomatic expressions, an interesting form of language and cul (...)